(untitled) (Al-Qantara, 2024)
This research explores the evolving academic landscape of Esports education, with a particular focus on the rationale and necessity for incorporating Esports courses into college curricula. The study aims to comprehensively analyze the key factors driving the development of Esports courses, shifting the conversation from the predominantly business-oriented view of Esports to the less examined academic perspective. Using a quantitative, descriptive approach, data was collected through questionnaires distributed to Esports companies and academic institutions. The findings reveal that both market and industry demand significantly influence the establishment of Esports and management courses in colleges. Moreover, the research highlights the critical role of societal culture in shaping the structure and content of these courses. Ultimately, this study provides a deeper understanding of the determinants that affect the creation and quality of Esports education. It offers valuable insights for academic institutions considering the introduction of Esports programs, emphasizing the need to align these courses with market demands and cultural considerations to enhance educational outcomes.